Evaluation of Carisolv™ for the Chemo–Mechanical Removal of Primary Root Caries in vivo - Fure, S.; Lingström, P.; Birkhed, D. (Caries research, 2000)
The objective of this study was to evaluate a new chemo–mechanical method (Carisolv™) for the removal of primary root caries in vivo in terms of efficiency, treatment time and patient perception. Thirty–eight patients participated in an open, randomised and controlled study. Of the 60 root carious lesions included, 34 were randomised for chemo–mechanical treatment and 26 for drilling. A within–subject comparison was used whenever the patient had two cavities, which was the case for 22 subjects. All the Carisolv–treated cavities became caries free, as did all but one of those treated with drilling, as judged by an independent examiner. Only 4 of 34 patients asked for anaesthesia in the Carisolv group compared with 6 of 26 patients in the drilling group. Of those who did not use anaesthesia, 12 individuals in the drilling group experienced some pain compared with none in the chemo–mechanical group (p<0.001). The mean treatment time for the Carisolv method was 5.9 ± 2.2 min, compared with 4.5 ± 2.0 min for drilling; time for anaesthesia excluded (p<0.05). No negative reactions or adverse effects were recorded during the study. All 55 teeth examined in the 1–year follow–up were found to be sensitive using an electric pulp tester, and there was no difference regarding the condition of fillings between the lesions treated with Carisolv and drilling. It can be concluded that root caries can be effectively removed using the Carisolv method. The longer treatment time was compensated by less need for anaesthesia.